Penyuluhan Mengenai Stroke – Apa dan Mengapa? - Lamhot Asnir Lumban Tobing (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The main goal of community education about stroke is to disaminate information in order to increase awareness of stroke including signs and symptoms, risk factors, appropriate emergency response, and effective prevention strategies. Extension activities provide an in-depth understanding of the dangers of dangerous blows and the importance of preventive measures through counseling media and seminars. This activity also seeks to provide assistance in recognizing early symptoms, treatment and management as early as possible, and education about a healthy lifestyle to reduce the risk of stroke. Thus, counseling about stroke is very important in reducing the incidence of stroke, early treatment, prevention and post-stroke rehabilitation to provide a better quality of life.